Phase II trail of nab-paclitaxel in metastatic breast cancer patients with visceral metastases - Yizhao Xie (BMC, 2021)
Abstract Background Visceral metastases account for 48–67% of metastatic breast cancer (MBC) patients and presage a worse overall survival. Previous study suggested potential effect of nab-paclitaxel on patients with visceral metastases subgroups. This phase II trial was conducted to explore the efficacy and safety of nab-paclitaxel in such a high-risk group of patients. Methods In this prospective, single-center, open-label, phase II study, MBC patients with visceral metastases (N = 80) received nab-paclitaxel (Abraxane, 125 mg/m2, D1, D8, D15 every 28 days). Results The median PFS was 5.1 months (95% CI: 4.2–6.0 months), with an ORR of 33.8% (95% CI 21.3–43.8%) and CBR of 66.2% (95% CI 56.3–75.0%). In univariate analysis, patients with premenopausal status had a trend of better treatment outcome. Multivariate analysis demonstrated non brain metastasis (adjusted HR 0.31, 95% CI 0.12–0.83, P = 0.019) and first line treatment (adjusted HR 0.37, 95% CI 0.17–0.81, P = 0.013) as independent predictors of longer PFS. The overall safety was acceptable with most common treatment-related, grade ≥ 3 toxicities of neutropenia (16.3%) and sensory neuropathy (3.7%). Conclusions This phase II trial documented satisfactory efficacy and safety of nab-paclitaxel in MBC patients with visceral metastases, providing evidence for relative clinical practice. Patients in first line therapy had better treatment outcome. For patients with premenopausal status or brain metastasis, further alternatives (for example, combined chemotherapy or targeting therapy) might be required. This study also demonstrated the efficacy and safety of 125 mg/m2 nab-paclitaxel among Asian patients. Trial registration This research is registered under clinicaltrials.gov (NCT 02687490, February 22, 2016).